A representação caleidoscópica da corporalidade da mulher negra em Um Defeito de Cor - Rossini, Tayza Cristina Nogueira (2014)
Traditionally, in social, historical, political and aesthetic spheres, the female was considered inferior to male. As a result of patriarchy politics, women were silenced, excluded and victimized by prejudice and stereotypes that were related to their corporeality and identity throughout history. In the literary and cultural field the female experience was not treated differently justifying the intensification of actions (in the middle of the 20th century) to raise the awareness of individuals about the need of deconstructing the women's oppression and marginalization. In this sense, the literature that starts to be produced by women raises a new perspective on the literary production represented until that time (male, white, heterosexual), bringing to the interior of the narrative voices previously absent, regarding to the production, as well as the representation of characters non-privileged before in the literary texts. Thus, the objective of this research is to analyze how the enslaved black woman is represented in the novel Um defeito de cor (2011), observing how the protagonist, Kehinde, courses her trajectory in a way to integrate herself with the ideologies and symbolic models culturally launched by white society in Brazil in the nineteenth-century. These changes reflect in the identity and corporeality of the protagonist allowing the observation of a kaleidoscopic representation, starting by an objectified body in the beginning of the trajectory, to a subjectified body at the end of what can be called via crucis of the body. Systematically scrutinized and categorized in the feminist studies, corporeality has contributed in discussions about the representation often related to stereotypes of objectification, besides legitimizing the domination by prejudices and stereotypes related to the image of women. Invisible bodies, subordinate bodies, disciplined bodies, violent bodies, eroticized bodies, reflected bodies and other bodies named by Elodia Xavier in her typology Que corpo é esse? O corpo no imaginário feminino (2007) help the research and analysis of the representation of the black female body in our corpus as well as the investigation and debate about the representation of the female body in the Brazilian literature written by women.